(untitled) (Philological Studies, 2021)
The paper demonstrates the possibilities of using the electronic dictionary “The Mythological Vocabulary of the Perm Region” in linguo-geographical research: in the areal aspect, nominations of the mermaid that have been noted in the region are considered. A corresponding linguistic map has been created with the help of the dictionary. The analysis shows that the all-Russian unit rusalka is the most widespread one in the region and has been recorded in the majority of its districts. Some areas form special nominations (chertovka, leshachikha, vodianaia, shishiga, poludnitsa). The rest of the names are local. The absence of names for the mermaid, common to the entire Perm territory, and the presence of many local nominations indicate the gradual loss of ideas about this character in the Permian mythological tradition. The commonality of the regional tradition is maintained only at the level of individual beliefs, not the language. Beliefs that are represented in the nominations of the mermaid and support the integrity of her image in the region include ideas about her demonic nature, her place of residence, the presence of her long hair, the prohibition to call her by her direct name and about the need to appease her. The advantage of the electronic dictionary “The Mythological Vocabulary of the Perm Region” when creating a linguistic map is the ability to go both from the vocabulary (through the section “Mythological character”) and from the geographical label (through the section “Geographic index of lexical units”). Both approaches make it possible to compile a map faster than when working with a paper dictionary, since the dictionary makes it possible to automatically either get a list of all mapped units, or not to refer to dictionary entries at all, but to work only with geographical labels.